The Presumption of Harm and Descriptions of Child Sexual Victimization: Sentencing the Victim-Offender - Arnold, Bronwyn (The British journal of criminology, 2025)
Child sexual abuse is presumed to be inherently harmful. During sentencing, the victim’s harm is relevant as a purpose for punishment and for determining the penalty, and the sentencing remarks communicate the reasons underpinning the offender’s punishment. This article explores a sample of sentencing remarks of sexually abused child sexual offenders made in three Australian jurisdictions between 2005 and 2018. It finds that the presumption of harm is routinely extended to the immediate victims, but rarely extended to victim-offenders. In some cases, judges used language which minimized the victim-offenders’ experiences. The article argues that the presumption of harm should be extended to victim-offenders and their harm acknowledged, to promote sentencing’s communicative function and help to facilitate its rehabilitative purpose.